Near full-length sequence analysis of a unique CRF01AE/B recombinant from Kuala Lumpur, Malaysia - Lau, K.A.; Wang, B.; Kamarulzaman, A.; Ng, K.P.; Saksena, N.K. (2007)
A new HIV-1 circulating recombinant form (CRF), CRF3301B, has been identified in Malaysia. Concurrently we found a unique recombinant form (URF), that is, the HIV-1 isolate 06MYKLD46, in Kuala Lumpur, Malaysia. It is composed of B or a Thai variant of the B subtype (B') and CRF01AE. Here, we determined the near full-length genome of the isolate 06MYKLD46 and performed detailed phylogenetic and bootscanning analyses to characterize its mosaic composition and to further confirm the subtype assignments. Although the majority of the 06MYKLD46 genome is CRF01AE, we found three short fragments of B or B' subtype inserted along the genome. These B or B' subtype regions were 716 and 335 bp, respectively, in the protease-reverse transcriptase (PR-RT) region, similar to those found in CRF3301B, as well as an extra 590 bp in the env gene region. Thus we suggest that 06MYKLD46 is a possible second-generation HIV-1 recombinant derived from CRF3301B.